Economic Potential and Market Prospects of MarSiBan: Local Probiotic Fermented Beverages for Functional Nutrition - Anastasia D’ Ornai (Masterpiece, 2025)
The increasing demand for clean and affordable energy has encouraged the exploration of locally sourced biomass alternatives, particularly in regions with abundant agricultural waste. Coconut fiber, one of Indonesia’s most prevalent organic residues, presents significant potential for conversion into renewable energy products. This study develops BioCOco, an organic briquette derived from coconut fiber, as an innovative solution to support community-based renewable energy initiatives. The research aims to evaluate the production process, physical characteristics, combustion performance, and community applicability of BioCOco. A mixed-methods approach was implemented, combining experimental laboratory testing with community participation workshops. The briquettes were produced using finely processed coconut fiber and natural starch-based binders, followed by controlled drying and compression. Laboratory results demonstrate that BioCOco possesses high calorific value, low smoke emissions, and strong material durability, meeting common standards for sustainable biomass briquettes. Community trials also indicate positive acceptance, driven by the briquette’s affordability, ease of ignition, and alignment with local environmental values. Additionally, the initiative fosters circular economy practices by transforming waste into a marketable energy product. This study concludes that BioCOco is a practical, low-cost, and environmentally responsible energy alternative for rural communities and holds strong potential for wider-scale adoption. Further research is recommended to optimize production technology and assess long-term socioeconomic impacts.